The challenges of speech therapy intervention in breastfeeding: an integrative review (Research, Society and Development, 2021)
The present study aimed to describe the main factors that interfere in breastfeeding with a focus on oral disorders and demonstrate how the speech therapy intervention is essential in this process. The methodology used consisted of an integrative review of the literature through the PubMed database, which included articles and studies referring to the last 5 years of publication (2015 to 2020), in Portuguese and English that addressed the theme related to the study in question. The studies corroborate that the speech therapy performance in breastfeeding provides the partnership that contributes to the maternal and child development. However, there is a need to detect the associated factors for intervention and proper management early. Thus, it is concluded that the work of the speech therapist with mothers and babies in the maternity ward is of fundamental importance, mainly to detect early the challenges for the establishment of healthy breastfeeding, and it is up to this professional to attend, listen and transmit to mothers information related to both breastfeeding and the implications for the proper development of newborns' oral structures.